3 - Trans-nationalizing the African Public Sphere: What Role for Trans-border Languages? - Barro, Maimouna (Africa Development, 2021)
At a time when the notion of ‘trans-national public spheres’ is gaining more and more currency in academic circles, the role played by languages, and trans-border languages in particular, cannot be ignored in our attempts to rethink the African public sphere. In the African context, language has been a major factor in determining cultural and ethnic identity among various groups, whether they live within the same nation-state or are territorially dispersed. This situation problematizes the idea of a Westphalian citizenry resident in a national territory, and challenges the assumption that lan- guages map onto states. This paper focuses on the Fulfulde language – a trans-border language spoken across several national boundaries in West Africa – and assesses ways in which trans-border languages contribute to the emergence of a transnational public sphere in Africa.